2007
DOI: 10.1002/adsc.200600587
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biaryls via Palladium‐Catalyzed [2+2+2] Cocyclization of Arynes and Diynes: Application to the Synthesis of Arylnaphthalene Lignans

Abstract: A novel method for construction of biaryls via palladium(0)-catalyzed [2 + 2 + 2] cocyclization of diynes and arynes was developed. By this [2 + 2 + 2] cocyclization, various arylnaphthalene derivatives, including a sterically hindered 2,2'-disubstituted-1,1'-binaphthyl, can be constructed by virtue of a variety of combinations of diynes and aryne precursors. Using this [2 + 2 + 2] cocyclization as a key step, the total syntheses of natural arylnaphthalene lignans, taiwanin C, taiwanin E, and dehydrodesoxypodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…For Pd-catalysed [2 + 2 + 2] cocyclization of diynes and arynes, see: Sato et al (2004Sato et al ( , 2007. For the biological activity of hydronaphtho[2,3-c]furan derivatives, see: Baldwin et al (1995); Takadoi et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
“…For Pd-catalysed [2 + 2 + 2] cocyclization of diynes and arynes, see: Sato et al (2004Sato et al ( , 2007. For the biological activity of hydronaphtho[2,3-c]furan derivatives, see: Baldwin et al (1995); Takadoi et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
“…[1,2] Numerous examples of an intermolecular or intramolecular [2+2+2] cycloaddition with alkynes or alkenes, as an unsaturated bond component, have been reported to date. [1,2] Numerous examples of an intermolecular or intramolecular [2+2+2] cycloaddition with alkynes or alkenes, as an unsaturated bond component, have been reported to date.…”
mentioning
confidence: 99%
“…
A transition metal-catalyzed [2+2+2] three-component cycloaddition is one of the most powerful methodologies for construction of a polycyclic skeleton in a one-pot operation. [1,2] Numerous examples of an intermolecular or intramolecular [2+2+2] cycloaddition with alkynes or alkenes, as an unsaturated bond component, have been reported to date. [1] However, [2+2+2] cycloaddition of substrates including an allene as a coupling partner is still limited to several examples.
…”
mentioning
confidence: 99%
“…Initially, a [2+2+2] cycloaddition of diyne 1a with the precursor 2a was investigated using a palladium catalyst according to the optimized conditions of the above-mentioned arynes. 5 However, the desired product 3a was not obtained, and 1a was recovered in 95% yield. After various attempts to 35 find a good catalyst for this reaction, it was found that nickel is suitable as a catalyst in the [2+2+2] cycloaddition of 3,4-pyridynes.…”
mentioning
confidence: 99%
“…1 In recent years, arynes have been utilized as substrates in [2+2+2] cycloaddition. [2][3][4][5] Pyridynes are the analogues of arynes containing a nitrogen in reactions and nucleophilic substitution reactions. 6 Compared with the extensive study on utilization of arynes in a [2+2+2] cycloaddition, the reactivity of pyridynes toward the [2+2+2] cycloaddition has not been studied at all.…”
mentioning
confidence: 99%